2016
DOI: 10.14797/mdcj-12-4-205
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Thromboembolic Pulmonary Hypertension: The Role of Medical Therapy and Balloon Pulmonary Angioplasty

Abstract: Chronic thromboembolic pulmonary hypertension (CTEPH) is a potentially curable disease when treated with pulmonary thromboendarterectomy (PTE). However, even at experienced surgical centers, nearly one-third of patients with CTEPH will be deemed inoperable for reasons including distal disease, comorbidities, or out-of-proportion pulmonary hypertension. It is in these patients with inoperable CTEPH that pulmonary hypertension (PH)-targeted medical therapy and balloon pulmonary angioplasty have potential therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
1
8
0
2
Order By: Relevance
“…The observed decline in TAPSE is in accordance with findings from other studies investigating the effect of PEA, and it is also found in patients undergoing general open heart surgery . Studies have suggested that the mechanism explaining the general reduction in TAPSE after open heart surgery may be associated with pericardiotomy, sternotomy itself, cardiopulmonary bypass, cardioplegia, or myocardial hypothermia . We also examined RV function by pulsed tissue Doppler of the lateral free wall using RV‐S′ which is another recognized parameter of RV systolic function.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The observed decline in TAPSE is in accordance with findings from other studies investigating the effect of PEA, and it is also found in patients undergoing general open heart surgery . Studies have suggested that the mechanism explaining the general reduction in TAPSE after open heart surgery may be associated with pericardiotomy, sternotomy itself, cardiopulmonary bypass, cardioplegia, or myocardial hypothermia . We also examined RV function by pulsed tissue Doppler of the lateral free wall using RV‐S′ which is another recognized parameter of RV systolic function.…”
Section: Discussionsupporting
confidence: 87%
“…Hemodynamic post‐PEA evaluation is often performed to assess the degree of normalization of pulmonary pressure and RV function to inform further treatment decisions, for example, specific vasoactive PH medication, renewed evaluation for second PEA, or balloon pulmonary angioplasty (BPA) treatment . Overall, our study demonstrated no major changes of RV systolic function from 3 to 12 months, indicating that post‐PEA evaluation can be performed already after 3 months.…”
Section: Discussionmentioning
confidence: 60%
“…BPA relies on the use of telescoping catheters placed in a central vein, through which wires and balloons are guided to mechanically disrupt chronic clot material and relieve pulmonary vascular obstruction. Recently, additional groups have reported that BPA improved symptoms and hemodynamic parameters in patients with peripheral‐type CTEPH . In addition, repeated PEA is not a feasible way due to high perioperative risk.…”
Section: Introductionmentioning
confidence: 99%
“…1 указан список исследований, посвященных изучению эффективности патогенетической терапии при ХТЭЛГ [42]. Современные методы лечения ХТЭЛГ С начала 60-х годов ХХ века и по сегодняшний день «золотым стандартом» лечения ХТЭЛГ остается операция двусторонней ТЭЭ, которая при успешном выполнении, помимо нормализации гемодинамических параметров и улучшения функционального статуса, позволяет обеспечить 5-летнюю выживаемость на уровне 74-89% [42,43]. По данным J. Lewczuk и соавт., 2-летняя выживаемость больных с ХТЭЛГ при срДЛА более 30 мм рт.ст., при отсутствии хирургического лечения составляет 12% [44].…”
Section: молекулярные механизмы развития хтэлг точки воздействия патunclassified